FEASIBILITY STUDY ON CONVENTIONAL CONCRETE AND CELLULAR LIGHT WEIGHT CONCRETE (FOAMED CONCRETE) - MR. PAVAN RANMALE (International Journal of Innovations in Engineering Research and Technology, 2021)
Lightweight Concrete is atype of concrete which contains anexpanding agent which increasesthe volume of the mixture while giving additional qualities such as nailbility and reducesthe dead weight. It is lighter than the conventional concreteused. Countries likeUSA, United Kingdom and Swedenhas been using lightweight concrete regularly in recent times. Lightweight Foamed Concrete2(LWC) has been successfully used and it has gained popularity due to its lower density than conventional concrete. It is created by uniform distribution of air bubbles throughout the mass of concrete. Recently, most studies on LWC concern on the influence of filler type and the particle size of sand on the strength. In this research, the strength of LWC with density 1600 kg/m3, 1800 kg/m3 and 2000 kg/m3was produceddue to different percentage of foam as aggregate replacement by Fly ash3. Lightweight Concrete has lowdensity as well as low thermal conductivity.